The TOPOS study - Sebastian, Tim; Barco, Stefano; Voci, Davide; Lichtenberg, Michael; Schlager, Oliver; Jalaie, Houman; Graaf, Rick de; Erbel, Christian; Massmann, Alexander; Schindewolf, Marc; Spirk, David (Vasa, 2024)
Background: We aimed to study the long-term safety and efficacy of oblique venous stents for post-thrombotic syndrome (PTS) with iliac vein compression. Patients and methods: In the multinational, prospective, single-arm TOPOS study, PTS patients scheduled for endovascular therapy with the sinus-Obliquus® stent and optional distal extension with the sinus-Venous® or sinus-XL Flex® stent were enrolled at eight European vascular centres between October 2016 and December 2020. The primary outcome was primary stent patency at 24 months, and secondary outcomes included the clinical course of PTS (Villalta score, revised Venous Clinical Severity Score [rVCSS], Visual Analog Scale [VAS] of pain), quality of life changes (Chronic Venous Insufficiency Quality of Life Questionnaire, CIVIQ-20), and device-related complications. Results: We enrolled 60 patients (mean age 46±15 years, 68% women, 13% active ulcers): 80% required stent extension (70% below the inguinal ligament). The primary patency rate at 24 months was 80.7% (95%CI 68.1–90.0%); it was higher in patients without vs. those with stent extension (90.9% vs. 78.3%, p=.01). Compared to baseline, the Villalta, rVCSS, pain VAS, and CIVIQ-20 decreased by a median of 8 (interquartile range (IQR): 4–11), 5 (IQR: 3–7), 3 (IQR: 2–5), and 17 (IQR: 6–22) points, respectively; p<.001 for all parameters. Overall, 9 events of acute stent occlusion, 4 symptomatic stent stenosis, and 1 pulmonary embolism occurred. We did not observe major bleeding events or contralateral thrombosis. Conclusions: Endovascular treatment with the oblique stent and optional stent extension was safe and resulted in high patency rates at 24 months. The reduction in PTS severity was substantial and persisted over 2-year follow-up.